Study of Unconfined Compressive Experiment on the Geogrid Flexible Reinforced Compound - Tong Jintian; Wang Wei (MATEC Web of Conferences, 2023)
In recent years, reinforced technique has been widely used in civil engineering technology. In order to deeply understand the behavior of the reinforced structure, this paper use the geogrid as the reinforced materials. The unconfined compressive tests were operated in the laboratory. The specimens were made by sharp sand which was classified according to the density at ρ=1.55g/cm3, ρ=1.75g/cm3, ρ=1.85g/cm3.Each specimen was reinforced with the layers of 0,1,2,3,4,5. Through analysis the experimental data, it’s founded that the density reinforced materials and the layers have an effect on the unconfined compressive strength. The specimen with bigger density and more reinforced layers has a better compressive strength. Different reinforced materials have different reinforced effect.